DIPLOMASI INDONESIA DALAM MENINGKATKAN EKSPOR MANGGIS KE TIONGKOK PERIODE 2013-2016 - Nuraziza Yuniarti, - (2018)
This study discusses diplomacy carried out by Indonesia in the face of a decline in mangosteen exports to China in the 2013-2016 period. Indonesia is one of the export producers of mangosteen and China is the main destination for Indonesian mangosteen exports. There was a decline in the volume of mangosteen exports in 2013 due to a decline in demand for mangosteen by China and due to obstacles. So the problem formulation of this research is how is Indonesia's diplomacy in increasing mangosteen exports to China in the period 2013-2016? This study uses the theory of diplomacy, international trade, the concept of non-tariff barriers, and national interests. In this study a qualitative descriptive method was used to explain the diplomatic efforts made by the Indonesian government in increasing mangosteen exports to China. The data sources used were divided into two, namely the first primary derived from research in the form of interviews and secondary data from books, journal articles related to this study. In conclusion, Indonesia has made various efforts, namely in the form of diplomacy to be able to re-export mangosteen from Indonesia to China and the results of mangosteen have been able to enter the Chinese market since last December 14, 2017